Interpretations of the ATLAS diboson anomaly - Kingman Cheung; Wai-Yee Keung; Po-Yan Tseng; Tzu-Chiang Yuan (Physics Letters B, 2015)
Recently, the ATLAS Collaboration recorded an interesting anomaly in diboson production with excesses at the diboson invariant mass around 2 TeV in boosted jets of all the WZ, W+W−, and ZZ channels. We offer a theoretical interpretation of the anomaly using a phenomenological right-handed model with extra W′ and Z′ bosons. Constraints from narrow total decay widths, dijet cross sections, and W/Z+H production are taken into account. We also comment on a few other possibilities.